The influence of performance appraisal practices on employee engagement at higher education institutions of Malaysia - Muslim Diekola Akanmu; Siti Aisyah Binti Panatik; Ruzanna Shahrin (Cogent Business & Management, 2025)
This study investigates performance appraisal practices (PAPs), such as performance feedback, financial reward, job promotion, performance recognition, and training and their respective influence on employee engagement and performance. Responses were gathered from 203 employees of Malaysian Higher Education Institutions (HEIs) using a stratified sampling technique while PLS-SEM was used as data analysis technique. The findings reveal that training and financial rewards significantly and positively affect employee engagement, while performance feedback, job promotion, and performance recognition have no significant influence on employee engagement. On the other hand, the results show a significant positive relationship between all PAPs and employee performance, except in the case of financial reward. Similarly, employee engagement has a significant effect on employee performance. This outcome suggests that there is a distinction between employee engagement and performance in academic settings. The study uncovers why there is a need for policy and decision makers in the education sector to focus more on how job promotion, performance feedback, and performance recognition can be optimized for job engagement among academic staff of Tertiary Institutions and financial rewards for effective employee performance.